Les colophons de Siméon de Płndzahank‘ du point de vue du problème de l’identité - Bozoyan, Azat (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
For the medievalist, the cultural world of the Caucasus presents a multifaceted and littlestudies issue of national identity. The material for my publication is the colophon records, associated with the literary activity of the translator Simeon of Plndzakhank’. In the 13th century, he translated from Georgian into Armenian the works of Proclus Diadochus, John Sinaiticus, etc. Memorable records of these translations contain exclusive records of several episodes of the activities of the famous translator. According to the surviving records, monk Simeon worked in the monastery of Gugark province or, as he notes, in the region of Lore (according to Georgian medieval sources – in the region of Somkhiti). This monastery came under the control of the Georgian Church in the 13th century through the intervention of Ivane Zakarian. Simeon was a Chalcedonian by confession, so he worked in the Church of ‘Georgians’. However, in his colophons he stressed: ‘For this purpose I have translated this [work], so that [the literature of] my people may have no gaps’ (‘յայն սակս թարքմանեցի, զի մի պակաս եղիցի սա յազգէս մերմէ’).